Matlab sımulatıon of quadcopter dynamıcs and PID attıtude controller - Safarov, Tural (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Due to the ever-growing popularity of quadcopters, they are used in various fields such as surveillance, military, surveillance and courier services and are of great importance. Ideal handling of quadcopters is essential for safe maneuvering and high precision flight performance. This research provides simulation of quadcopter control in MATLAB software, development and review of various control principles. Dynamic development in unmanned aerial vehicles (UAVs) has led to the rapid spread of quadcopters in many fields, from airspace control to courier services. This research study investigates the Proportional-Integral-Derivative (PID) attitude controller by simulating the quadcopter dynamic object in MATLAB software. The heart of this research is to create and develop a PID attitude controller, which is a critical component for accurate control of quadcopter.